The effect of structure and swelling of concrete on the frequency of acoustic emission signals - KOŁTOŃSKI, W. (Archives of Acoustics, 1992)
In this paper results of experimental studies on the relationship between fundamental frequency of acoustic emission signals and time of water percolation into cement as well as its structure, are presented and discussed. Possibilities of practical application of this relationship for use in the building industry have been indicated.